Men's squash (Tufts Archival Research Center, 2015)
photographic print. Top row (left to right): Coach Bill Summers, Todd Abedon, Dan Horan, Chris Waldorf, Andy Obermeier, Jon Segal, Coach Jim Watson. Front row (left to right):All American Rusty Hashim, Josh Lebowitz, Captain John Penotti, Dan Joseph (Capt. Elect) Mike Gordon.